Marine Automatic Weather System (MAWS) instrumentation system for climate change monitoring based on The Internet of Things (IoT) - Husen Zakaria; Ismail Nazli; Syukri Surbakti Muhammad; Omar Fairuz; Yusibani Elin; Kesuma Fatmawati; Nurhanif Nurhanif; Arif Hasibuan Ahmad; Fauzi Fauzi (BIO Web of Conferences)
This research is based on the need for Marine Automatic Weather Station (MAWS) devices for climate change monitoring based on the Internet of Things (IoT) which are still lacking and are supplied from abroad. This research is limited to wind speed and direction parameters. The resulting wind speed and direction data will be saved into a database and displayed on a 16x2 LCD and a dynamic website using PHP, CSS, HTML, JavaScript, and SQL programming. The data transmission is using the 2G/3G cellular network so that the device could be placed in areas where there is only a 2G/3G cellular network. This instrumentation system consists of several parts, such as a data processing unit using the Arduino Uno microcontroller. This instrument is also equipped with a SIM808 GSM/GPRS/GPS module. In this research, there are two stages of equipment testing, i.e. laboratory testing to determine whether data can be sent in real-time into the database, and field testing which functions to calibrate the equipment. The error value of the wind speed measuring instrument is 2.48 % and the accuracy is 97.52%, so the designed instrument can be said to be accurate. Meanwhile, the wind direction measuring instrument has a high error value of 21.93 % and an accuracy of 78.07%.